A study of Preventing Concurrency’s Problems using 2-Phase Locking Protocols (2-PL) - Singh, Anil Kumar (International Journal of Computer Sciences and Engineering, 2018)
Now days every organization has importance of time in its day to day working. To save time, the task should be executed in distributed manner and also to adopt the procedure to perform, parallel or concurrent execution method. Concurrency means, more than one transactions are performing at the same time then they are interleaving to each other. When the transactions are inter-leaving for short span they cause the different types of problems like lost update, dirty read etc. To control these types of problems, there are several methods like Locking Methods, Time-stamp Methods and Optimistic Methods. In this paper we will study the 2-Phase Locking Protocol which comes under locking method. With the help of 2-PL, we shall reveal how to prevent the problem arise due to concurrency with the help of suitable examples. It will help the students and research scholars to understand that how to prevent the concurrency problems with the help of 2-Phase Locking Protocol (2-PL) method